Relationships Between Fungal Contamination and Some Physicochemical Properties of Rapeseeds - Janda Katarzyna; Markowska-Szczupak Agata (Ekológia (Bratislava), 2015)
The aim of this study was to evaluate some properties of rapeseed, to determine the amount of fungi including thermotolerant and xerophilic species and to specify the correlations between some physical properties of rapeseed and the number of fungi. Material was 18 samples of rapeseeds. The characteristics of seeds included volumetric weight, impurities, pH, moisture, water activity, fat content, fat acidity and critical moisture of seeds. Number of fungi were investigated on RBA, YpSs, DG18 medium at 25, 37 and 45°C. Differences between amount of rapeseed impurities and fat acidity have been revealed. The number of fungi was diversified depending on medium and incubation temperature. The largest fungi number was isolated on DG18 at 25°C. Correlations between physicochemical properties of seeds and number of isolated fungi have been pointed out. Our study demonstrated that low pH values and weight by volume of seeds as well as high acidity of fat can be used as indicators of contamination of rapeseeds by fungi.